2022
DOI: 10.3390/pathogens11111339
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antiprotozoal Evaluation of New Promising 2,9-Bis[(substituted-aminomethyl)]-4,7-phenyl-1,10-phenanthroline Derivatives, a Potential Alternative Scaffold to Drug Efflux

Abstract: A series of novel 2,9-bis[(substituted-aminomethyl)]-4,7-phenyl-1,10-phenanthroline derivatives was designed, synthesized, and evaluated in vitro against three protozoan parasites (Plasmodium falciparum, Leishmania donovani and Trypanosoma brucei brucei). Pharmacological results showed antiprotozoal activity with IC50 values in the sub and μM range. In addition, the in vitro cytotoxicity of these original molecules was assessed with human HepG2 cells. The substituted diphenylphenanthroline 1l was identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The intermediate 1,3,5-tris[(4-formylphenyl)methyl]benzene 2 was prepared by a triple Suzuki-Miyaura cross-coupling reaction of 1,3,5-tris(bromomethylbenzene with an excess of 4-formylphenylboronic acid in the presence of Pd(PPh 3 ) 4 and sodium carbonate [28,29]. The reaction of various primary substituted alkylaminoalkylamines with trialdehyde 2 led to the 1,3,5-tris[(4-(substituted-iminomethyl)phenyl)methyl]benzenes 3a-r, which were then reduced into the 1,3,5-tris[(4-(substituted-aminomethyl)phenyl)methyl]benzene derivatives 4a-r by using sodium borohydride in methanol, as previously described by our team [17][18][19][20]. These new 1,3,5-tris[(4-(substituted-aminomethyl)phenyl)methyl]benzene derivatives 4a-r were then converted into ammonium oxalate salts 1a-r by reaction with oxalic acid in isopropanol.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate 1,3,5-tris[(4-formylphenyl)methyl]benzene 2 was prepared by a triple Suzuki-Miyaura cross-coupling reaction of 1,3,5-tris(bromomethylbenzene with an excess of 4-formylphenylboronic acid in the presence of Pd(PPh 3 ) 4 and sodium carbonate [28,29]. The reaction of various primary substituted alkylaminoalkylamines with trialdehyde 2 led to the 1,3,5-tris[(4-(substituted-iminomethyl)phenyl)methyl]benzenes 3a-r, which were then reduced into the 1,3,5-tris[(4-(substituted-aminomethyl)phenyl)methyl]benzene derivatives 4a-r by using sodium borohydride in methanol, as previously described by our team [17][18][19][20]. These new 1,3,5-tris[(4-(substituted-aminomethyl)phenyl)methyl]benzene derivatives 4a-r were then converted into ammonium oxalate salts 1a-r by reaction with oxalic acid in isopropanol.…”
Section: Chemistrymentioning
confidence: 99%
“…During our research, we focused on the discovery of novel aza heterocyclic compounds that can be useful in antiprotozoal chemotherapy [12][13][14][15][16][17][18][19][20]; we have formerly developed various series of 2,9-bis[(substituted-aminomethyl)phenyl]phenanthrolines (series A-B), 2,4-bis[(substituted-aminomethyl)phenyl]quinolines, 1,3-bis[(substituted-aminomethyl) phenyl]isoquinoline and 2,4-bis[(substituted-aminomethyl)phenyl]quinazoline derivatives (series C) designed as antiprotozoal candidates, which could bind to Plasmodium falciparum DNA G-quadruplexes [17][18][19][20] in order to bypass the resistance mechanisms deployed by the parasites and also based on efflux. Indeed, it has previously been described that the telomeres of various protozoa could constitute attractive drug targets [21][22][23][24], and telomerase activity is observed in gametocytes and during the transition to the erythrocytic stage of the parasite P. falciparum [25].…”
Section: Introductionmentioning
confidence: 99%
“…Because phen is planar, rigid, and hydrophobic, it can intercalate within DNA base pairs. , In addition, phen and appropriately substituted derivatives phen sub have been successfully used to stabilize a specific guanine tetrameric structure, the so-called “G-quadruplex”, with potential applications as anti-cancer drugs . Finally, phen belongs to the vast family of molecules featuring anti-mycoplasmal and anti-malarial activity. , …”
Section: Introductionmentioning
confidence: 99%
“…[34,35] We found that sugar conjugated naphthalene diimides previously shown to be G4 ligands [36] also bind G4s found exclusively in T. brucei and present very notable antiparasitic activity. [33,37,38] Eventually, other quadruplex ligands such as quarfloxin, CX-5461 [39] and compounds based on stiff stilbene, [40] naphthalene diimide, [41] perylene diimide, [42] phenantroline, [43,44] quinoxaline [45] and quinoline scaffolds [46] have been reported with antitrypanosomal and antiplasmodial activity. [47] In this work, we studied the presence of PQS in the genome of Trypanosoma cruzi and carried out biophysical studies confirming that some of these frequent PQS actually form stable quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%